Room temperature infrared imaging sensors based on highly purified semiconducting carbon nanotubes1. Issue 15 (21st April 2015) - Liu, Yang; Wei, Nan; Zhao, Qingliang; Zhang, Dehui; Wang, Sheng; Peng, Lian-Mao
<x xml:space="preserve">Abstract</x> A carbon nanotube infrared imaging sensor is constructed with highly-purified semiconducting nanotube films.